Hybridity in the governance and delivery of public services - Bonomi Savignon, Andrea; Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Studies in public and non-profit governance, 2018)
The concept of hybridity, although well developed in various research areas, is relatively new in the management field, where organisational hybridity( refers to organisations that combine managerial features, value systems and institutional logics of different sectors (market, state, civil society). Hybrid organisations have traditionally been compared with private, public and non-profit ones, by considering goal ambiguity, governance, organisational structures, personnel and purchasing processes, and work-related attitudes and values. This research has led to substantial evidence on relevant differences between hybrid and other organisations. Hybridisation has also become a permanent feature in todays welfare system. New Public Management and welfare state reforms of the mid 1990s contributed to the emergence of hybrid organisations, with neo-institutional theory also attributed to this phenomenon. Considering the hybrid phenomenon as a whole, little is known about governance and controls, especially with regard to accountability mechanisms and issues such as the prevention of corruption. Even less is known when we consider the main variables of hybridity to be mixed ownership, competing institutional logics, multiplicity of funding arrangements, and public and private forms of financial and social control.This book seeks to answer the unsolved questions related to hybrid organisations. It does so by adopting a multifaceted approach along its ten chapters, which focus on different national contexts, including the UK, Italy, Australia, and Sweden, as well as global organisations. The authors consider policy sectors including humanitarian aid, local transport, healthcare, and welfare services.